The Effects Of Acid Dipping And In-Pack Pasteurization On The Safety And Quality Of Fresh Rice Noodles - Low, Yan Kitt (2020)
Fresh rice noodles have short shelf life of not more than 3 days due to microbial risk and starch retrogradation. In this study, the preservation of fresh rice noodles using glucono-delta lactone (GDL) as dipping bath acidulant and in-pack pasteurization was elucidated. It was hypothesized that when GDL solubilizes in water, a low pH system with mild tart flavour would be a good dipping bath acidulant for fresh rice noodles. Whereas in-pack pasteurization that involves vacuum packaging and thermal processing can further enhance the preservation effects on the fresh rice noodles.